Stability Analysis and Clustering of Electrical Transmission Systems - Brato, Sebastian; Surmann, Dirk; Krey, Sebastian; Götze, Jürgen; Ligges, Uwe; Weihs, Claus (Technische Universität Dortmund, 2014)
A proper understanding and modelling of the behaviour of heavily loaded large-scale electrical transmission systems is essential for a secure and uninterrupted operation. In this paper we present a descriptive analysis especially of low frequency oscillations within an electricity network and methods to assess the stability of the whole system based on an ARMAX model and the ESPRIT algorithm. Further we present two methods to separate the network into local areas, which is necessary for an efficient modelling of a large electrical system. The first method has its foundation in the results of the ARMAX based stability analysis and the second method concentrates on the network topology. In the last part of this paper we present an approach how an modelling of such local areas within an large electrical system based on stochastic differential equation models is possible.
Keywords: statistics; spectral clustering; ARMAX; power network; electricity network; stability analysis; graph; signal analysis; clustering; 004; 310; 620